2018
DOI: 10.1016/j.bbi.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute versus chronic stress on ethanol sensitivity: Evidence for interactions on both behavioral and neuroimmune outcomes

Abstract: Acute alcohol intoxication induces significant alterations in brain cytokines. Since stress challenges also profoundly impact central cytokine expression, these experiments examined the influence of acute and chronic stress on ethanol-induced brain cytokine responses. In Experiment 1, adult male rats were exposed to acute footshock. After a post-stress recovery interval of 0, 2, 4, or 24 h, rats were administered ethanol (4 g/kg; intragastric), with trunk blood and brains collected 3 h later. In non-stressed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 121 publications
(158 reference statements)
1
15
0
Order By: Relevance
“…Nevertheless, the finding that hippocampal c-Fos was more strongly induced by footshock CED group raises many questions about how the HPC is modulated by the CED procedure, and highlights this region as highly plastic in responding to predictable stressors. Indeed, other work from our laboratory has recently demonstrated that acute footshock exposure led to enhanced IL-6 responses evoked by acute ethanol intoxication, whereas CED exposure led to a blunted increase in hippocampal IL-6 as well as altered behavioral sensitivity to ethanol-induced loss of righting reflex ( Doremus-Fitzwater et al, 2018 ). Furthermore, the transition of the brain toward a more inflamed state during later stages of natural aging might be accelerated by life history of stressful events, as stress early in life is a known threat to natural aging ( Bale and Epperson, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the finding that hippocampal c-Fos was more strongly induced by footshock CED group raises many questions about how the HPC is modulated by the CED procedure, and highlights this region as highly plastic in responding to predictable stressors. Indeed, other work from our laboratory has recently demonstrated that acute footshock exposure led to enhanced IL-6 responses evoked by acute ethanol intoxication, whereas CED exposure led to a blunted increase in hippocampal IL-6 as well as altered behavioral sensitivity to ethanol-induced loss of righting reflex ( Doremus-Fitzwater et al, 2018 ). Furthermore, the transition of the brain toward a more inflamed state during later stages of natural aging might be accelerated by life history of stressful events, as stress early in life is a known threat to natural aging ( Bale and Epperson, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore critical to develop highly tractable models of chronic stress in which the underlying physiological mechanisms of adaptation and ultimately, adverse health consequences of stress can be studied effectively. Toward this end, a wide variety of acute stress models are commonly utilized to study the underlying neural and hormonal consequences of stress, and may have important implications for understanding sensitivity to alcohol ( Doremus-Fitzwater et al, 2018 ) and natural aging processes ( Bale and Epperson, 2015 ). To model chronic stress experienced by humans, investigators often assemble daily stress challenges to specifically manipulate psychological features of the stressful experience, including the controllability ( Maier et al, 1986 ), predictability ( Weiss, 1970 ), duration ( Martí et al, 1994 ), and general intensity ( Natelson et al, 1988 ) of the stressful circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have demonstrated that in some cases, following alcohol exposure, immune proteins act as important signaling molecules in the brain in addition to their role in the periphery (Crews et al, ; Szabo and Lippai, ). For example, repeated cycles of exposure and/or larger doses of alcohol (Crews, ; Marshall et al, ; Peng et al, ; Zahr et al, ; Zhao et al, ) are known to produce a long‐lasting induction of neuroimmune genes as well as increases in levels of serum cytokines (Crews and Vetreno, ; Doremus‐Fitzwater et al, ; Doremus‐Fitzwater et al, ; Zou and Crews, ). Several preclinical studies have additionally demonstrated that adolescent alcohol exposure can also induce neuroinflammatory changes (Crews and Vetreno, ; Crews et al, ; Guerri and Pascual, ; Montesinos et al, ; Pascual et al, ).…”
mentioning
confidence: 99%
“…Yet, an acute binge‐like EtOH challenge resulted in increased IL‐6 gene expression during EtOH intoxication and suppression of IL‐1β and TNF‐α, whereas clearance (withdrawal) of EtOH saw these effects reversed within 12 to 18 hours of EtOH administration (Doremus‐Fitzwater et al., , 2015; Gano et al., ). Additionally, the expression of IL‐6, but not other cytokines, was strongly influenced by prior EtOH exposure (Doremus‐Fitzwater et al., ), the schedule of EtOH exposure (Gano et al., ), and recent stress history (Doremus‐Fitzwater et al., ). Thus, the time‐dependent effects of EtOH on a multitude of cytokines suggest there would be great value in the ability to assess continuous cytokine protein changes following EtOH exposure in awake, behaving rats.…”
mentioning
confidence: 99%